ANALISIS PENGARUH BUDAYA ORGANISASI, SERVANT LEADERSHIP, & KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada Karyawan Hotel Grasia Semarang) - Prasetyo, Kongko Dwi; Mas’ud, Fuad (Diponegoro Journal of Management, 2021)
This study aims to examine and analyze the influence of organizational culture, servant leadership, and organizational commitment to organizational citizenship behavior of employees at Hotel Grasia Semarang. This research was conducted by giving questionnaires to 66 respondents. This study used SPSS Statistic 25 software analysis tool. The test data used included validity, reliability, classical assumption, t test, F test, coefficient of termination, and multiple linear regression analysis. .Based on the results of the instrument test, it is known that all the instruments in this study are valid and reliable. In testing the classical assumptions also showed that the data were normally distributed, there were no symptoms of multicolonearity and no symptoms of heterocedasticity. Based on the results of regression analysis, show that the equation Y = 0.332 X1 + 0.409 X2 + 0.171 X3. The coefficient of determination shows the number 0.565, which means the dependent variable is influenced by the independent variable by 56.5%.The results showed that organizational culture has a positive and significant effect on organizational citizenship behavior of employees, servant leadership has a positive and significant effect on employee organizational citizenship behavior, and organizational commitment has no effect on organizational citizenship behavior of employees.Â